2019
DOI: 10.1108/ecam-10-2018-0451
|View full text |Cite
|
Sign up to set email alerts
|

Job satisfaction of project managers in green construction projects

Abstract: Purpose Green building is a promising approach to improve resource efficiency and achieving sustainable development. The success of green construction projects is closely associated with the performance of project managers (PMs), while job satisfaction plays a major role in the performance of PMs. However, the emphasis placed on the job satisfaction of PMs in green construction projects remains minimal. The purpose of this paper is to identify the relationships between the job satisfaction of PMs and its key i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 44 publications
(52 reference statements)
0
7
0
Order By: Relevance
“…Many researchers have attempted to examine the effects of personal, work and organisational factors on job satisfaction of different cohort of workforces in the industry. While there are studies that focussed on all construction professionals in general, some recent works have specifically focussed on project managers (e.g., Ling et al, 2018;Hwang, Zhao and Lim, 2019;), architects (e.g., Sang, Ison and Dainty 2009), quantity surveyors (e.g., Bowen and Cattell, 2008;Lian and Ling, 2018), craftworkers (e.g., Albattah et al, 2016;Shan et al, 2016;Oo, Liu and Lim, 2020), and labourers (e.g., Hosseini, Chileshe and Zillante, 2014;Hsu and Liao, 2016). However, there is little or no study on job satisfaction of early career women or new female CM graduate hires in the construction industry.…”
Section: Women's Career Expectations and Job Satisfaction In Construcmentioning
confidence: 99%
“…Many researchers have attempted to examine the effects of personal, work and organisational factors on job satisfaction of different cohort of workforces in the industry. While there are studies that focussed on all construction professionals in general, some recent works have specifically focussed on project managers (e.g., Ling et al, 2018;Hwang, Zhao and Lim, 2019;), architects (e.g., Sang, Ison and Dainty 2009), quantity surveyors (e.g., Bowen and Cattell, 2008;Lian and Ling, 2018), craftworkers (e.g., Albattah et al, 2016;Shan et al, 2016;Oo, Liu and Lim, 2020), and labourers (e.g., Hosseini, Chileshe and Zillante, 2014;Hsu and Liao, 2016). However, there is little or no study on job satisfaction of early career women or new female CM graduate hires in the construction industry.…”
Section: Women's Career Expectations and Job Satisfaction In Construcmentioning
confidence: 99%
“…Task performance and contextual performance together comprise employees' overall performance. It has been shown that employees' high participation in an organization's decision-making process can improve the connection between personal goals and organizational goals (Hwang et al , 2019). Tightening this connection will reduce any role conflict or cognitive dissonance, further reduce employees' stress and lead to better JP.…”
Section: Research Hypothesesmentioning
confidence: 99%
“…Job satisfaction and job performance have been an important research topic in the AEC (Architecture, Engineering and Construction) industry, and many researchers have explored their relationship with various elements from personal aspects, e.g. pay rate, promotion opportunity and working hours (Sang et al , 2009), job stress and burnout (Leung et al , 2011; Wu et al , 2019), job content and resource adequacy (Hwang et al , 2019), work–home interference, fairness of rewards (Sun et al , 2020), to more abstract elements at organizational level, e.g. personal-organisational value conflicts (Panahi et al , 2016), HR management practices (Ling et al , 2018), external coordination and client management (Salvatierra et al , 2019), knowledge sharing and organizational commitment (Sang et al , 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In alignment with the resource-based view, which defines resources as any organizational characteristic that can constitute either a strength or a weakness (Wernerfetlt, 1984), ECPMs serve as an organizational strength to construction employers whose work is performed through projects (Borg and Scott-Young, 2020b). Both the RBV and the SHRM theory (Lepak and Snell, 2002) regard ECPMs as a valuable and rare resource, given their criticality to construction project success (Hwang et al, 2020) and the current shortage of project managers and projected growing demand worldwide (Project Management Institute, 2017). In addition, the lengthy formation period of four years of university study, means that unlike the lowvalue, non-unique construction trades and manual workforce, project management professionals are not readily replaceable.…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Project managers are essential to the initiation, planning, control and execution of the project management process, which is critical for successful project delivery (Hwang et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%